The role of Chinese Muslims in Islamisation of Malaysia: expectations and challenges - Mahmud, Mek Wok; Shah Haneef, Sayed Sikandar; Fatah Yasin, Raudlotul Firdaus (IIUM Press, 2018)
Reversion to Islam while opening golden opportunities for a revert in terms of divine guidance and spiritual salvation is coming with somewhat insurmountable challenges in terms of Islamization of the self, family and contributions to the overall development of Malaysia as a multi-religious country. This is especially so when Islam as an official religion has made the issue of Islamization of the Malaysian society and its systems amongst the pivotal national agendas in the country. As to what is the role of Chinese Muslims (reverts) in the process, studies, among others, have purported to present the statistics about their share in socioeconomic development. Similarly, empirical studies point to the odds faced by this community at personal, family and community levels in their path for transition to the full Islamic way of life. To the presenters of this paper, however, the macro dimension of what it means to become a Muslim which is essential for adjustment to the Islamic requirements has not been sufficiently high-lighted in discourses in the area. Accordingly, this paper presents the position statements on Islamic expectations from Chinese reverts with the purpose of motivating them to achieve greater things in the area of Islamization of their community and the nation to the effect.